Paleoproterozoic evolution of the eastern Alxa Block, westernmost North China: Evidence from in situ zircon U–Pb dating and Hf–O isotopes - Dan, W.; Li, X.; Guo, J.; Liu, Y.; Wang, Xuan-Ce (Elsevier Science BV, 2012)
The Alxa Block is the westernmost part of the North China Craton (NCC). In the past, it has been considered to be part of the Archean NCC. However, formation and evolution of this block remain poorly understood, and this has hampered a broader understanding of the NCC. In this study we analyzed the in situ zircon U–Pb age and Hf–O isotopes for the two oldest rock units in the eastern Alxa Block, namely the Bayanwulashan and Diebusige Complexes. The Bayanwulashan Complex consists mainly of metamorphic rocks with mafic and felsic protoliths. SIMS U–Pb zircon dating results indicate that the primary magmatic ages of the mafic and felsic igneous rocks are ca. 2.34 Ga and ca. 2.32–2.30 Ga, respectively, and both sets of rocks were overprinted by two metamorphic events at ca. 1.89 Ga and ca. 1.79 Ga. Geochemical and zircon Hf–O isotopic data suggest that the ca. 2.34 Ga amphibolites within the Bayanwulashan Complex are characteristically high in TiO2 (up to 3.2%), Zr (up to 394 ppm) and Ti/V (> 30), resembling the basaltic rocks formed within continental rifts. The ca. 2.32–2.30 Ga felsic rocks were generated by remelting of dominant meta-igneous rocks that have zircon Hf model ages of 2.92–2.81 Ga. The Diebusige Complex is composed of amphibolites, mafic gneisses and paragneisses. It was intruded by granites dated at ca. 1.97–1.98 Ga, and subjected to high grade metamorphic events at ca. 1.89 Ga and ca. 1.79 Ga. Re-examination of U–Pb ages for detrital and metamorphic zircons indicate that the depositional ages of protoliths of the Diebusige paragneisses may be considered to be between ca. 2.45 and 2.0 Ga. These U–Pb zircon age data do not support the existence of exposed Archean rocks in the eastern Alxa Block, although the possibility of Archean rocks at deeper crustal levels cannot be ruled out entirely.The eastern Alxa Block contrasts to the neighboring Yinshan Block and Khondlite Belt, as well as the Trans-North China Orogen, in terms of the timing and evolution of magmatism and metamorphism. Thus, we conclude that the Alxa Block is a separated Paleoproterozoic terrane from the Western Block of the NCC, rather than the western extension of the Yinshan Block or part of the Khondalite Belt, as previously proposed.